Pengaruh Brand Image dan Electronic Word of Mouth Terhadap Niat Beli Mobil Honda dengan Sikap Konsumen Sebagai Variabel Moderasi - Siska Anzelin; Istiharini; Theresia Gunawan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study examines the influence of brand image and electronic word of mouth (e-WOM) on purchase intention of Honda Cars, with consumer attitude as a moderating variable. Using a quantitative approach, data were collected from 140 respondents through questionnaires. The analysis technique used is SEM-PLS with SmartPLS 4.0. The results show that brand image and e-wom positively and significantly influence purchase intention. Consumer attitude does not significantly moderates the relationship between brand image and purchase intention, nor does it significantly moderate the relationship between e-Wom and purchase intention. The findings suggest that managing digital reputation and enhancing consumer perceptions are vital for increasing Honda’s market share.